Використання нейронних мереж для створення та обробки відеоконтенту - Ішу, А. О. (ХНУРЕ, 2024)
The article examines key aspects of the use of neural networks in the field of video processing. The work discusses neural networks and their main principles of operation. Particular attention is paid to image generators based on neural net orks, diffusion models, highlighting their effectiveness in creating and optimizing video content. The features of stable diffusion are explored and modern ser vices based on this technology are presented. This work is aimed at unlocking the potential of neural networks in video production and indicating ways for their optimal use.
Keywords: створення відеоконтенту; обробка відеоконтенту